2004
DOI: 10.1136/vr.154.16.501
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the feed intake, pH and osmolality of rumen fluid, and the position of the abomasum of eight dairy cows during a dietinduced left displacement of the abomasum

Abstract: During the last six weeks of the dry period, eight Holstein-Friesian cows were fed a restricted amount of grass silage; after calving, a mixture of maize silage and concentrates was offered in a feeding regimen designed to induce a displacement of the abomasum. In the first month after calving, the cows were monitored for the following variables: feed intake and composition, milk production, the position of the abomasum, and the pH and osmolality of the rumen contents. In five of the eight cows, a left displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…We found that high corn silage plus distillers' grain diets during pregnancy may be related to an increase in postpartum morbidity, especially from ketosis, metritis, abomasal displacement and retained placenta. It has been shown that high corn silage diets can increase the incidence of abomasal displacement (Van Winden et al, 2004). Similarly, with diets containing high corn silage (18.2 kg/day), cows are more likely to develop ketosis, metritis, and retained placenta (Holter et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…We found that high corn silage plus distillers' grain diets during pregnancy may be related to an increase in postpartum morbidity, especially from ketosis, metritis, abomasal displacement and retained placenta. It has been shown that high corn silage diets can increase the incidence of abomasal displacement (Van Winden et al, 2004). Similarly, with diets containing high corn silage (18.2 kg/day), cows are more likely to develop ketosis, metritis, and retained placenta (Holter et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisadores ressaltam a importante associação entre o balanço energético negativo no pré-parto refletindo um aumento na concentração de ácidos graxos não esterificados e o deslocamento de abomaso para esquerda (Cameron et al, 1998, Van Winden et al, 2004. Portanto, dentro os principais fatores de risco relacionados ao manejo nutricional no período pré-parto de vacas e consequentemente ao balanço energético negativo: elevado níveis de condição corporal, inadequado fornecimento de dieta, dietas altamente energéticas e estações de inverno e PUBVET v.11, n.7, p.680-688, Jul., 2017…”
Section: Fatores De Riscounclassified
“…Although the unique structure of the archaeal cell membrane enables them to be more stress tolerant than rumen bacteria [ 9 ], they still require optimal rumen temperature (38°C to 41°C) and osmolality (260 to 340 mOsmol kg −1 ) for growth and metabolism [ 10 ]. Both physicochemical parameters are sensitive to a number of external factors in the rumen of livestock animals including the use of different dietary components, which possess an ability to resiliently change the osmotic pressure as well as rumen temperature [ 11 , 12 ]. The consequences of such stressors on the rumen archaea population range from cellular dehydration [ 13 , 14 ], to single-cell death [ 15 ], to a complete disruption of fermentation in the rumen ecosystem resulting in ruminal dysbiosis and a reduction in animal production and health [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%